Community Compliance In Compliance With Post-Vaccination Health Protocol In West Nusa Tenggara Province - Zulkieflimansyah; Nurjihadi, Muhammad; Wahyudi, Agus; Muhammad Rizqi, Reza; Nur Fietroh, Muhammad (Publisher Cv. Inara, 2022)
This study aims to assess the extent to which the people of West Nusa Tenggara adhere to the health protocol after the first and second doses of vaccination. This research is quantitative descriptive. The collection technique used a questionnaire. For data analysis using the three box method. The results showed that the obedience index of the people of West Nusa Tenggara in complying with health protocols during the post-vaccination Covid-19 pandemic was in the high category.